pH changes after manual or ultrasonic instrumentation and smear layer removal with EDTA or ultrasonic - Zampronio, Camila Fonseca [UNESP]; Sivieri-Araujo, Gustavo [UNESP]; Bonetti-Filho, Idomeo [UNESP]; Camargo Villela Berbert, Fabio Luiz [UNESP] (Wiley-Blackwell, 2008)
The purpose of the present study was to evaluate the influence of instrumentation techniques associated with the smear layer removal, in the pH changes of the root surface. Thirty mandibular humans premolars were divided into three groups: Group I - instrumentation by Ohio technique and final cleaning with EDTA (3 minutes); Group II - instrumentation by Ohio technique and final cleaning with ultrasonic (1 minute); Group III - instrumentation by the ultrasonic technique and final cleaning with ultrasonic (1 minute). The pH was measured in the cavities prepared in the cervical, middle and apical thirds of the lateral wall of each root. The teeth were evaluated at the initiation of the experiment, and 3, 7, 14, 21, 30 days after of the intracanal dressing of the calcium hydroxide with camphorated p-monochlorophenol (Calen/PMCC). All the groups presented increasing pH values; group III presented the highest average pH, followed by groups II and I; the values for the apical third were lower than those of the middle and cervical thirds (ANOVA and Tukey test). The results showed that the biomechanical preparation by the ultrasonic technique and smear layer removal with ultrasonic showing the highest diffusion of the calcium and hydroxyl ions from the intracanal dressing (P < 0.05).